The Relationship Between The Learning Outcomes Of Entrepreneurship Courses And Student Entrepreneurial Motivation - Faiza, Ardiana; Yulastri, Asmar; Syarif, Wirnelis; Siregar, Juliana (Universitas Negeri Padang, 2024)
This research is motivated because the higher the learning outcomes of entrepreneurship courses, the higher the entrepreneurial motivation of students. The purpose of this study is to describe the learning outcomes of entrepreneurship courses with the entrepreneurial motivation of Family Welfare Education students. This type of research is Descriptive Quantitative with a Correlational Approach. The research was conducted at the Department of Family Welfare, Faculty of Tourism and Hospitality, Padang State University. The student population was 314 people and the sample was 76 people using the Random Sampling Sampling Technique. The source of the research data is students of the Family Welfare Education Study Program who have taken entrepreneurship courses. Data collection techniques using Questionnaires or Questionnaires are measured using Likert Scale. Data Analysis techniques are carried out by Correlation Coefficient Analysis and Correlation Coefficient Test. The results illustrate that the Entrepreneurship Learning Outcomes of Family Welfare Education Study Program students are in the Very Good Category, namely With Praise with Frequency Results of 29 (39%), and the Entrepreneurial Motivation of Family Welfare Education Students as a whole is included in the Medium Category of 26 (35%). Based on the hypothesis test, there is positive and significant relationship between the learning outcomes of the Entrepreneurship Course and the Entrepreneurial Motivation of Family Welfare Education Students with the results of the score obtaining a significant value of 0.03.